2015
DOI: 10.1255/jnirs.1187
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control of Ginkgo Biloba Leaves by Real Time Release Testing in Combination with near Infrared Spectroscopy

Abstract: Ginkgo leaves are widely utilised in Chinese herbal medicines and functional food additives. However, the quality of ginkgo leaves fluctuates obviously due to the variety of geographical environments and climate conditions. Real time release testing (RTRT) combined with near infrared (NIR) spectroscopy was used to improve the quality control of ginkgo leaves. The RTRT of ginkgo leaves was achieved by qualitative and quantitative analysis using NIR spectroscopy and acceptable releasing criteria. Partial least s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In the past few years, near-infrared (NIR) spectroscopy has developed rapidly as a non-destructive testing technique that has the characteristics of convenient analytical instruments, 8 no sample preparation, 9,10 and real-time monitoring. 11,12 NIR is widely used in food, [13][14][15] medicine, 16,17 and other elds. With chemometric analysis and machine learning on NIR spectroscopic data, objects can be quickly compared and identied.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, near-infrared (NIR) spectroscopy has developed rapidly as a non-destructive testing technique that has the characteristics of convenient analytical instruments, 8 no sample preparation, 9,10 and real-time monitoring. 11,12 NIR is widely used in food, [13][14][15] medicine, 16,17 and other elds. With chemometric analysis and machine learning on NIR spectroscopic data, objects can be quickly compared and identied.…”
Section: Introductionmentioning
confidence: 99%
“…Li (2018) used hyperspectral data to estimate nutrient elements in the leaves and canopy of Pyrus sinkiangensis 'Kuerlexiangli'. Liu et al (2022) identified anthracnose and black spot of pear leaves on near-infrared hyper spectroscopy.…”
Section: Introductionmentioning
confidence: 99%